Halal Supply Chain Management pada Bisnis Pariwisata - Hamid, Hammas Hubaibi Akbar El Hamid; Balqis Salsabila; Mushthofa Akhyar (Islamic Economics and Business Review, 2024)
Abstract Tourism is an economic sector that continues to grow, and more and more tourism business players are realizing the importance of integrating tourism aspects, including halal aspects, in their operations. This article reviews the concept and application of Halal Supply Chain Management (HSCM) in the tourism business. This research uses a descriptive qualitative method using a literature study approach sourced from relevant documents, magazines, scientific articles, books, and so on. The results of the discussion in this paper are that the application of the halal supply chain management concept requires all parties involved, including tourists, tourism businesses, travel agents, hotel providers, entertainment facility providers, and others, to comply with sharia principles. Sharia principles include avoiding polytheism, immorality, mafsadat, tabdzir and evil. The opportunities and challenges that exist in the implementation of halal tourism need to be studied to achieve maslahat and support the Indonesian Islamic Economic Masterplan. Keywords: Halal; Supply Chain Management; Tourism   Abstrak Pariwisata adalah sektor ekonomi yang terus berkembang, dan semakin banyak pelaku bisnis pariwisata yang menyadari pentingnya mengintegrasikan aspek keberlanjutan, termasuk aspek kehalalan, dalam operasional mereka. Artikel ini mengulas konsep dan penerapan Halal Supply Chain Management (HSCM) atau manajemen rantai pasokan halal dalam bisnis pariwisata. Penelitian ini menggunakan metode kualitatif deskriptif menggunakan pendekatan studi pustaka yang bersumber dari dokumen, majalah, artikel ilmiah, buku, dan sebagainya yang relevan. Hasil pembahasan pada tulisan ini bahwa penerapan konsep halal supply chain management menuntut agar semua pihak terlibat, termasuk wisatawan, pelaku usaha pariwisata, biro perjalanan, penyedia hotel, penyedia fasilitas hiburan, dan lainnya, untuk mematuhi prinsip-prinsip syariah. Prinsip syariah tersebut seperti terhindar dari kemusyrikan, maksiat, mafsadat, tabdzir, dan munkar. Peluang dan tantangan yang terdapat pada penerapan pariwisata halal perlu dikaji untuk mencapai kemaslahatan dan mendukung Masterplan Ekonomi Syariah Indonesia. Kata kunci: Halal; Manajemen Rantai Pasok; Pariwisata